Paleocene postgenetic Accumulation of Nannoplankton on the Phillipsite Minerals in Roo Rise, Indian Ocean - Mimin Karmini Adisaputra; Dida Kusnida (Indonesian Journal on Geoscience, 2010)
DOI: 10.17014/ijog.v5i1.92The sample studied was derived from the base of core MD 982156, one of the boreholes obtained during the IMAGES Expedition. The expedition was carried out as a research cooperation between Indonesia and French Governments using Marion Dufresne Research Vessel, belonging to IFRTP (French Institute for Polar Research). Within this sample, the phillipsite minerals were firstly found by the first author. Using SEM (Scanning Electron Microscope) at the magnification of x1,000 for group and up to x20,000 for individual photos, the nannoplanktons were shown to accumulate on the phillipsite minerals as a binding matrix. Different directions and velocity of the bottom current when the phillipsite minerals were originated, might have contributed in binding of the various mineral shapes. The calcareous nannoplankton in the studied area is preserved within the sediments between 3880 m to 3914 m depths below sea level (bsl). This interval possibly located between Lysocline and Carbonate Compensation Depth (CCD), is indicated by the presence of well preserved calcite minerals and calcareous nannoplankton within sediments. Discoaster multiradiatus, the dominant fossil within the sediments in the studied area, is Paleocene in age. Therefore, the binding of nannoplakton accumulation as a matrix of the phillipsite minerals occurred as a postgenetic deposition.